Affordable unmanned aerial vehicle aircraft for surveillance - Sidek, Shahrul Na'im; Mokhtar, Mohd Ismail; Mohamad Khalil, Abdul Mushawwir (2010)
Unmanned aerial vehicle (UAV) has been used in defense, traffic monitoring, down to agricultural sector. However, the UAV is usually very expensive and not accessible by public. In this work, we develop a UAV, designed to perform surveillance job at a lower cost to make it affordable for personal use as well as for research purposes. The UAV is able to record video of ambient conditions using wireless camera and locate itself using GPS module to enable real-time video streaming and flight path tracking on 'Google Map'. The UAV possesses two different flight modes namely manually-controlled and auto-pilot modes. By means of RC Joystick, it can be manually maneuvered and with auto-pilot mode, it will autonomously navigate its way to the designated coordinate based on the GPS unit. We use thermopile sensor to stabilize and maintain the UAVs altitude during its autonomous navigation. The entire structure is made of styrofoam backboned by carbon fiber tube and wooden stick to make it light weight, easy to maneuver, replaceable and cost efficient.